Software para estimativa do custo operacional da maquinaria agrícola MAQCONTROL - Piacentini, Liane (2007)
This work describes the development of a software for farm machinery operation cost calculation, once the use of machines and agricultural implements are one of the factors that demand larger operational costs. Those costs are divided in fixed and variable costs. The objective of this work was to develop a software (MAQCONTROL) that contributed in the process of determination of these costs in an agile and precise way. In the development of the system preliminary calculations had been carried through, calculations of fixed and changeable costs and the capacity of operational field. The fixed costs were determinated for the expenses with depreciation, interests, shelter and insurances. With variable costs, it was given emphasis at the costs of the maintenance, such as: lubrification, filters, tires, grease, fuel, small repairs and exchange of parts. In the software validation were used harvest data from a period of two years, from an agricultural property located in the city of Cascavel, PR. With the processed information it was possible the obtaining of the operational cost (R$ ha-1) and of the operational capacity (ha h-1) of the crop operation.